2018
DOI: 10.3389/fmicb.2018.01736
|View full text |Cite
|
Sign up to set email alerts
|

Dietary L-Tryptophan Modulates the Structural and Functional Composition of the Intestinal Microbiome in Weaned Piglets

Abstract: Background: Intestinal microbiota plays an important role in regulating metabolism, physiology, and immune response of the host. L-Tryptophan (Trp) are metabolized by several genera of bacteria. It remains largely unknown whether Trp can regulate the composition and diversity of the intestinal microbiota and contribute to intestinal homeostasis.Methods: A total of 126 weaning piglets were fed a corn- and soybean meal-based diet supplemented with 0, 0.2, or 0.4% Trp for 4 weeks. The intestinal microbiota was me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
98
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 112 publications
(105 citation statements)
references
References 67 publications
7
98
0
Order By: Relevance
“…Interesting, we found dietary 0.2% Trp alleviated the decrease of alpha diversity in ileum microbiota challenged by LPS, but dietary 0.4% has no effect on the reduction of diversity in ileum microbiota caused by LPS. This result consistent with a previous study, which reported the richness and diversity of gut microbiota in 0.2% Trp group higher than that in control and 0.4% Trp groups [19]. These results indicated that the addition of 0.2% Trp to the diet has improved regulation of ileum microbiota diversity than 0.4% Trp treatments regardless of whether the piglets are challenged by LPS.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Interesting, we found dietary 0.2% Trp alleviated the decrease of alpha diversity in ileum microbiota challenged by LPS, but dietary 0.4% has no effect on the reduction of diversity in ileum microbiota caused by LPS. This result consistent with a previous study, which reported the richness and diversity of gut microbiota in 0.2% Trp group higher than that in control and 0.4% Trp groups [19]. These results indicated that the addition of 0.2% Trp to the diet has improved regulation of ileum microbiota diversity than 0.4% Trp treatments regardless of whether the piglets are challenged by LPS.…”
Section: Discussionsupporting
confidence: 92%
“…Some previous studies have shown that dietary Trp level could regulate feed intake [15], growth [16], intestinal integrity [17] and oxidative stress [14] of pigs. Interestingly, recent studies reported that dietary Trp altered intestinal microbial composition and diversity, improved intestinal barrier and downregulated expression of inflammatory cytokines in the intestine of weaned piglets [18,19]. In addition, increasing dietary tryptophan level could improve feed intake and growth performance of weanling pigs orally challenged with Escherichia coli K88 [16].…”
mentioning
confidence: 99%
“…In other words, starch digestion in the small intestines of ruminants can be modulated by the environment inside of the small intestine. It is while a similar phenomenon was previously reported in broiler chicks [11] and weaned piglets [12]. Therefore, any attempts to improve α-amylase activity in duodenal fluids could help starch digestion, which is also targeted in the present study.…”
Section: Introductionsupporting
confidence: 82%
“…Indeed, a growing evidence implicates gut microbiota-derived metabolites as active modulators, encompassing diet, microorganisms, and the host, attributed to causal functionality, including SCFAs and tryptophan metabolites [19,25]. Tryptophan metabolites in particular have been shown to affect the development of NAFLD by altering the composition of the gut microbiota [5,26]. Indole compounds are major products of tryptophan-derived metabolites, and include indole-3-acrylic acid, indole-3-acetic acid, and indole-3-propionic acid [5,7,20].…”
Section: Discussionmentioning
confidence: 99%